The level of reflective thinking among mathematics teachers of the first three school classes in Jordan - Alkhazam, Awad Mufleh (Arab Journal for Sciences and Research Publishing, 2020)
The study was designed to identify the level of reflective thinking among mathematics teachers for the first three school classes in the light of the variables of educational experience and educational qualification., The study population of all the mathematics teachers for the first three grades in the public schools in the province of Mafraq in Jordan during the first semester of the academic year 2018/2019 and the number (835) teachers. The study sample consisted of (500) mathematics teachers for the first three school classes. The study included a questionnaire consisting of (30) paragraph of Eysenck and Wilson reflective thinking scale (Eysenck & Wilson, 1976), which Barakat (2005) Arabized and developed and reformulated to suit the Arab environment. The researcher used descriptive analytical method in the survey, The results of the study showed that the level of reflective thinking among mathematics teachers for the first three school classes was medium on the whole scale, where the mean was( 1.35. The results also showed statistically significant differences (0.05≥α) In the level of reflective thinking of mathematics teachers for the first three grades due to the teaching experience and for the benefit of teachers with teaching experience (more than 5 years), The results also showed that there were statistically significant differences ( 0.05 ≥α ) in the level of reflective thinking among the mathematics teachers for the first three school classes due to the scientific qualification and to the benefit of teachers with qualification (higher than Bachelor).
Keywords: Reflective Thinking; Mathematics Teachers; Grades 1-3